The association of vitamin A, zinc and copper levels with clinical symptoms in children with autism spectrum disorders in Jilin Province, China - Junyan Feng; Ling Shan; Chunyue Miao; Yang Xue; Xiaojing Yue; Feiyong Jia (BMC, 2023)
Abstract Background This study evaluated vitamin A (VA), copper (Cu), and zinc (Zn) levels in the population with autism spectrum disorder (ASD) in Jilin Province, China. Furthermore, we examined their links to core symptoms and neurodevelopment, as well as gastrointestinal (GI) comorbidities and sleep disorders. Methods This study included 181 children with autism and 205 typically developing (TD) children. The participants had not taken vitamin/mineral supplements in the prior three months. High-performance liquid chromatography was used to measure serum VA levels. By using inductively coupled plasma-mass spectrometry, Zn and Cu concentrations in plasma were determined. Importantly, the Childhood Autism Rating Scale, the Social Responsiveness Scale, and the Autism Behavior Checklist were used to measure core ASD symptoms. However, the Griffith Mental Development Scales-Chinese were used to measure neurodevelopment. GI comorbidities and sleep abnormalities were assessed with the 6 Item-Gastrointestinal Severity Index and Children's Sleep Habits Questionnaire, respectively. Children with ASD with GI issues were grouped according to severity (low GI severity and high GI severity groups). Results (i) The difference in VA, Zn, Cu levels and the Zn/Cu ratio between ASD and TD children is small. But children with ASD had lower VA levels and Zn/Cu ratio, higher Cu levels than TD children. Cu levels in children with ASD were associated with the severity of core symptoms. (ii) Children with ASD were much more likely than their TD counterparts to suffer from GI comorbidities or sleep problems. Furthermore, it was observed that high GI severity was associated with lower levels of VA, whereas low GI severity was associated with higher levels of VA. (iii) The children with ASD who had both lower VA and lower Zn/Cu ratio had more severe scores on the Autism Behavior Checklist, but not on other measures. Conclusion Children with ASD had lower VA and Zn/Cu ratio, and higher Cu levels. Cu levels in children with ASD were weakly correlated with one subscale on social or self-help. ASD children with lower VA levels may face more serious GI comorbidities. Children with ASD combined VA-Zn/Cu lower had more severe core symptoms. Trial registration Registration number: ChiCTR-OPC-17013502. Date of registration: 2017-11-23.